AirAsia Malaysia : the IPO decision - Jena, Sanjay Ketan, 1958- (SAGE business cases., 2020)
The case, "AirAsia Malaysia: The IPO Decision," presents the situation faced by Tony Fernandes, founder and CEO of AirAsia Berhad (AAB), when he and his team of senior managers had to decide whether they should raise funds through an initial public offer (IPO) or through private equity. The airline started operations in January 2002 and became debt-free within eight months. It earned a net profit of RM 49 million on a revenue of RM 392.7 million in 2004. The AAB planned to buy planes and augment its fleet of 17 aircraft. Fernandes wanted to replicate his low-cost model in other countries as well. In November 2003, he entered into a collaboration with the Shin Corporation of Thailand to start a budget carrier there. The team needed RM 800 million to buy more aircraft to expand its business. Going public would mean a greater administrative burden on the small team of managers. Fernandes had the choice of going through private placement and raising funds, which would mean control in the hands of a few as opposed to diffused control in a public offer. In this context, he wondered what could be done.